2009
DOI: 10.1521/psyc.2009.72.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Treatment of Psychotic Symptoms: Spiritists Compared to Mental Health Professionals in Puerto Rico and Brazil

Abstract: This article expands psychosocial and cultural perspectives on the experience and expression of psychotic symptoms and the treatment of schizophrenia by exploring how Spiritism, a popular religion in Latin America, provides healing to persons with severe mental illness. Beliefs and treatment by Spiritist healers of persons with psychotic symptoms, some diagnosed with schizophrenia, are described. Reactions by mental health professionals (psychologists, mental health technicians and psychiatrists) to this alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 2 publications
0
15
0
2
Order By: Relevance
“…However, participants who were not Buddhist had also consulted a tâng‐ki (shaman) for help. The explanation that one was possessed by a ghost indicated that one was being manipulated by an external evil power, rather than succumbing to personal flaws (Moreira‐Almeida & Koss‐Chioino ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, participants who were not Buddhist had also consulted a tâng‐ki (shaman) for help. The explanation that one was possessed by a ghost indicated that one was being manipulated by an external evil power, rather than succumbing to personal flaws (Moreira‐Almeida & Koss‐Chioino ).…”
Section: Resultsmentioning
confidence: 99%
“…Attributions in relation to possession by a ghost or the influences of karma are widely reported in Taiwan, Thailand, Puerto Rico and Brazil (Lin et al . , Loue & Sajatovic , Moreira‐Almeida & Koss‐Chioino , Sanseeha et al . , Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Such sources included traditional and spiritual practices provided by spiritual/traditional/faith healers in eight articles and/or Western treatment methods provided by mental health professionals in five articles. Examples of treatment methods by spiritual/traditional healers included use of alternative medicines, ‘dissuading the obsessing spirit of its purpose to do harm,’ spiritual cleanses, and communication with ancestral spirits (Furnham & Igboaka, 2007; Furnham & Wong, 2007; Moreira-Almeida & Koss-Chioino, 2009 ; Mzimkulu & Simbayi, 2006; Teuton et al, 2007). In the five articles that preferred treatment methods by mental health providers, services included psychotherapy, medication, and hospitalization (De Toledo Piza Peluso & Blay, 2009; Harland et al, 2009; Kim-Goh, 1993; Milstein et al, 2000; Motlana, et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Many of these themes fell into the context of spiritualist belief systems which are prevalent in many Latino cultures and are not considered “abnormal” or “uncommon.” In some cases, these beliefs may actually represent a spiritual gift as opposed to a clinical disorder. (Gaviria & Wintrob, 1976; Moreira-Almeida & Koss-Chioino, 2009). …”
Section: Discussionmentioning
confidence: 99%